2018
DOI: 10.1039/c8cp02535e
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of surfaces states at cubic perovskite (001) surfaces by CO2 adsorption

Abstract: By using first-principles approach, the interaction of CO2 with (001) surfaces of six cubic ABO3 perovskites (A = Ba, Sr and B = Ti, Zr, Hf) is studied in detail. We show that CO2 adsorption results in the formation of highly stable CO3-like complexes with similar geometries for all investigated compounds. This reaction leads to the suppression of the surfaces states, opening the band gaps of the slab systems up to the corresponding bulk energy limits. For most AO-terminated ABO3(001) perovskite surfaces, a CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…O 1s XPS peaks in the spectrum of the PbTiO 3 nanocatalyst collected after exposure to CO 2 gas were rarely different from their counterparts in the spectrum collected pre-exposure. The XPS peaks of Ba, Sr, and Ca indicated that CO 2 chemisorption at A-metal sites (Ba and Ca > Sr) was preferred over chemisorption at Ti sites due to their lower adsorption energies Figure S37b shows the ratios of produced carbon to A-site atoms (C/A; A = Ba, Sr, Ca, or Pb).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…O 1s XPS peaks in the spectrum of the PbTiO 3 nanocatalyst collected after exposure to CO 2 gas were rarely different from their counterparts in the spectrum collected pre-exposure. The XPS peaks of Ba, Sr, and Ca indicated that CO 2 chemisorption at A-metal sites (Ba and Ca > Sr) was preferred over chemisorption at Ti sites due to their lower adsorption energies Figure S37b shows the ratios of produced carbon to A-site atoms (C/A; A = Ba, Sr, Ca, or Pb).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The mechanism of CO 2 reduction into nanodiamond and graphitic structures on the nanocatalysts shown in Figure was estimated by CO 2 chemisorption and reaction mechanism on perovskite-type materials in the preceding works, as mentioned below. A CO 2 chemisorption site was evaluted from ab initio calculations on (001) surfaces of ABO 3 perovskite . CO 2 was highly stable to be adsorbed on A sites with a CO 3 -like complex rather than on B sites.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that CO 2 molecules can suppress the surface states of SiO 2 , which is consistent with previous research. 64,65 Meanwhile, they can also activate new electronic energy states via carbonation reaction.…”
Section: Resultsmentioning
confidence: 99%